Nietzsche, Truth and Transformation - Mitcheson, K. author. aut Link
IX, 188 p.
Keywords: Providing a novel interpretation of Nietzsche's philosophical method, Nietzsche, Truth and Transformation addresses the philosophical problem of on what basis, if knowledge is always from a perspective, one can criticise modern humanity and culture, and how such critique can be actively responded to.